2016
DOI: 10.1074/jbc.m116.740092
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Macrophage CD36 Expression and Cellular Oxidized Low Density Lipoprotein (oxLDL) Accumulation by Tamoxifen

Abstract: Macrophage CD36 binds and internalizes oxidized low density lipoprotein (oxLDL) to facilitate foam cell formation. CD36 expression is activated by peroxisome proliferator-activated receptor ␥ (PPAR␥). Tamoxifen, an anti-breast cancer medicine, has demonstrated pleiotropic functions including cardioprotection with unfully elucidated mechanisms. In this study, we determined that treatment of ApoE-deficient mice with tamoxifen reduced atherosclerosis, which was associated with decreased CD36 and PPAR␥ expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…PPARγ is a type II nuclear receptor that works as a transcription factor by forming a heterodimer with retinoid X receptor (RXR), recruiting coactivators or corepressors based on ligand binding, and modulating gene transcription via binding to PPARγ response elements (PPREs) in the promoters of genes [18]. Two genes that have been identified to have promoter PPREs are PPARGC1A [41], which encodes the protein PGC1α, and CD36 [42][43][44]. These proteins may serve as biomarkers of PPARγ target engagement.…”
Section: Can Target Engagement Of Pparγ By Pioglitazone Be Detected Imentioning
confidence: 99%
“…PPARγ is a type II nuclear receptor that works as a transcription factor by forming a heterodimer with retinoid X receptor (RXR), recruiting coactivators or corepressors based on ligand binding, and modulating gene transcription via binding to PPARγ response elements (PPREs) in the promoters of genes [18]. Two genes that have been identified to have promoter PPREs are PPARGC1A [41], which encodes the protein PGC1α, and CD36 [42][43][44]. These proteins may serve as biomarkers of PPARγ target engagement.…”
Section: Can Target Engagement Of Pparγ By Pioglitazone Be Detected Imentioning
confidence: 99%
“…Several studies have demonstrated that increased PPAR γ can upregulate CD36 expression and function, while PPAR γ knockout can dramatically reduce CD36 expression and function in many different types of cells, including macrophages, hepatocytes, and kidney cells [2427]. As a nuclear transcription factor, PPAR γ can be regulated by many factors and then up- or downregulate CD36 expression and function.…”
Section: Introductionmentioning
confidence: 99%
“…We cannot definitively explain the observation that CD36 mRNA expression in whole liver extracts appeared to increase after LD feeding (Fig. 5C), although we recognize that other, nonhepatocyte populations (macrophages and Kupffer cells) express CD36 (17), and it is plausible that LD feeding induces adaptive increases in CD36 expression in these cell types. However, this possibility remains to be tested experimentally.…”
Section: Discussionmentioning
confidence: 80%
“…high-fat diet-induced obesity and other findings that adenoviral-mediated hepatic CD36 overexpression increased hepatic FFA uptake and steatosis (14). In addition, CD36 has been shown to regulate cholesterol uptake, utilization, and secretion from both the small intestine (15,16) and mouse peritoneal macrophages (17).…”
mentioning
confidence: 90%